2011
DOI: 10.5114/aoms.2011.24139
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of thyroid function during pregnancy: the advantage of self-sequential longitudinal reference intervals

Abstract: IntroductionTo evaluate clinical value of a new self-sequential longitudinal reference intervals of thyroid function during pregnancy.Material and methodsWe established two different series of reference intervals: self-sequential longitudinal reference intervals (SLRI) and general gestation-specific reference intervals (GSRI). For SLRI, the serum of 301 cases were collected five times in every case throughout the gestation. For GSRI, A total of 1455 subjects included in the study. We collected the serum respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Direct comparison of our data to other published reports is problematic, as TFT reference intervals can be influenced by diet, maternal age, and assay methodology [e.g., 5,9,10,15]. It is well documented in the literature that using non-pregnant adult reference intervals to interpret TFT in pregnant women has the potential to result in a large number of misclassified test results [e.g., 6,7]. For these reasons, the American Thyroid Association (ATA) recommends using trimester specific reference intervals established in a population with optimal iodine intake [5].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Direct comparison of our data to other published reports is problematic, as TFT reference intervals can be influenced by diet, maternal age, and assay methodology [e.g., 5,9,10,15]. It is well documented in the literature that using non-pregnant adult reference intervals to interpret TFT in pregnant women has the potential to result in a large number of misclassified test results [e.g., 6,7]. For these reasons, the American Thyroid Association (ATA) recommends using trimester specific reference intervals established in a population with optimal iodine intake [5].…”
Section: Discussionmentioning
confidence: 81%
“…Failure to do so can lead to potential misclassification of thyroid function tests (TFT) results in pregnant women [6,7]. Ideally, clinical laboratory test performance should be characterized using specimens representative of the patient population which the laboratory serves [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have established that the ranges of thyroid stimulating hormone (TSH) and free thyroxine (FT4) concentrations during pregnancy are lower than in non-pregnant women. FT4 levels are below the non-pregnant reference range in a substantial minority of pregnant women (Kurioka et al, 2005; Cotzias et al, 2008; Yu et al, 2010; Wang et al, 2011; Yan et al, 2011). The usual negative correlation between TSH and FT4 in non-pregnant women is lost during later pregnancy (Kurioka et al, 2005; Jonklass et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…THs are essential for normal neonatal development in both humans and rodents [3,23,[101][102][103][104] and the experimental work indicated that THs are transported from the mother to the fetus, albeit in limited amounts, and that the fetal brain is exposed to THs before initiation of fetal TH synthesis [1]. In addition, the maternal TH regulates early fetal brain development in human and animal models [2].…”
Section: Maternal-fetal Thyroid In Normal Statementioning
confidence: 99%